Turismo sexual infantojuvenil: um desafio para a educação popular - Cunha, Roseana Cavalcanti da (2014)
The debate about children and juvenile sexual tourism is inserted in the scientific field of social sciences, drawing on the contributions of Educational Sciences, due to its complexity and social importance - expression of violation of ethical and human principles. In this paper, the implication of sexual tourism education has signaled as thread; demonstrate that popular education constitutes assumption to face sexual tourism of children and adolescents. For this purpose, a logical sequence based on an analysis of how the infant-juvenile sex tourism falls within tourism is sought, showing the philosophical basis for dialogue with the Popular Education with Paulo Freire in arguing for coping actions and examine proposals for education Planos Estaduais de Enfrentamento da Violência Sexual and NGOs working in the northeast face the infantojuvenil sex tourism. The debate has expanded to Latin American and Brazilian authors with theoretical and methodological perspective in dialectical bases, who participated in the resistance struggles in history. It is a descriptive qualitative research characterized as a case study on the phenomenon of infant-juvenile sexual exploitation through tourism in Brazil, focusing on the northeast as a research field with an eye toward the states with the highest incidence of ESCA and NGOs experience working in this perspective with pedagogical practices of coping. It is put in motion perspective, based on the concreteness of sexual exploitation phenomenon for the argument thought about children and juvenile sexual tourism in its confrontation. It was used as an instrument of data collection semi-structured interview, in addition to scientific journals and indexing combined with the existing literature as sources for critical appraisal. In the course of research and its considerations assume the contradictory nature of the research object within a social fabric in which the situation analysis of social struggles occupies on the one hand, public spaces to take on the construction of citizenship, but otherwise coexists with the existence of a silent network in a reverse way, in violation of established rights. Popular Education as a theoretical and epistemological assumption, to face the children and juvenile sexual tourism, mediated dialogue on human communicative interaction guided by socio-anthropological arguments, defines the human condition to be "relationships" with a view to liberating education in process coping children and juvenile sexual tourism.